THE INFLUENCE OF SOCIAL MEDIA AND EASY ACCESS TO THE INTERNET AND ITS CONSEQUENCES FOR BRAZILIAN ADOLESCENTS AND YOUNG PEOPLE - Sgarbosa, Lorenzo; Pinto, Giuliano Scombatti (Revista Interface Tecnológica, 2022)
This article is a study carried out with Brazilian youth and adolescents about the use of the internet and especially social networks. The study is characterized as exploratory, quantitative, carried out with 100 young people and adolescents from the region of Ribeirão Preto/SP, with emphasis on the city of Guariba/SP. For data collection, a questionnaire was used with questions about the use of the internet and social networks, in which we sought to understand more about the behavior in relation to this use, and how it has affected the respondents. It seeks to bring a reflection about this cyberspace and try to observe how the exacerbated use of it can cause harm to young people and adolescents. From the research carried out, it is possible to identify an unruly use by the majority, which does not fully satisfy the respondents. And it becomes increasingly necessary to raise awareness of the use both for teenagers and for their parents, who can follow and understand the seriousness of this virtual life of their children.